Analysis of the Strength of Looks of Female Politician Candidates "Case Study of the Last Election in Jambi Province" - Asriyadi, Asriyadi; Fradesa, Fiza; Arifullah, Mohd. (PERSPEKTIF, 2024)
This study aims to analyze the impact of the strength of appearance capital on voter perceptions and its contribution to the success of female political candidates in the Jambi Province General Election. Appearance capital includes physical appearance, attractiveness, and other visual elements. This research uses a qualitative method with a descriptive type with a purposive sampling technique. Data collection was carried out through field studies and literature studies. Informants in this research included Jambi female politicians, academics, political observers, and the Jambi community. Researchers took these informants because they were considered the best in providing the information needed. The findings show that, although appearance capital can influence initial perceptions, other factors such as background, experience and political vision still play a crucial role in determining a candidate's success. This research can contribute in the form of new insights regarding the understanding of women's political participation in Jambi Province.